Bond tests and on-site structural concrete quality control - Lorrain, Michel; Barbosa, Mônica Pinto [UNESP]; Arnaud, Maurice (My University, 2010)
Quality control of structural concrete has been conducted for decades using the axial compression test. The Pull-Out Bond test is suggested here as an alternative to the axial compression test of concrete. Well known and operated since the very beginning of reinforced concrete, this test provides the bond strength between concrete and reinforcement. The compressive strength of concrete has been shown to be closely related to the bond strength. This correlation may be used to check the strength of concrete from the results given by bond tests. This idea, applied in several locations under very severe technical conditions gave results which fairly fitted the correlation laws. This already confirms the capacity of the Pull-Out Bond Test to become a quality control test of reinforced concrete.
Keywords: Bond strength; Concrete compressive strength; On-site test; Pull-out test; Quality control of concrete